2017
DOI: 10.1007/s00107-017-1257-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization of wood treated with a formulation based on propolis, caffeine and organosilanes

Abstract: The aim of the study was to present chemical characteristics of a potential wood protection system composed of three chemical components. The paper presents preliminary results of chemical and biological analysis of wood treated with a mixture of 30% ethanol extract of propolis, caffeine and organosilanes: methyltrimetoxysilane (MTMOS) and octyltriethoxysilane (OTEOS). The sapwood of Scots pine (Pinus sylvestris L.) was impregnated with the above mentioned solution by vacuum method. The samples of wood treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…The weight loss of the wood treated with chitosan oligomers and propolis after 30 days of exposure to T. versicolor was 32.8% compared to 42.3% of the weight loss of the untreated wood [33]. The pine wood impregnated with the preparation consisting of propolis extract, caffeine and organosilanes (methyltrimethoxysilane and octyltrimethoxysilane) was five times more resistant against the activity of C. puteana than the unprotected samples [34]. The earlier work of authors indicated that pine wood treated with the extract of Polish propolis with silicon compounds was more durable against C. puteana than untreated wood [36,39].…”
Section: Decay Testmentioning
confidence: 94%
See 2 more Smart Citations
“…The weight loss of the wood treated with chitosan oligomers and propolis after 30 days of exposure to T. versicolor was 32.8% compared to 42.3% of the weight loss of the untreated wood [33]. The pine wood impregnated with the preparation consisting of propolis extract, caffeine and organosilanes (methyltrimethoxysilane and octyltrimethoxysilane) was five times more resistant against the activity of C. puteana than the unprotected samples [34]. The earlier work of authors indicated that pine wood treated with the extract of Polish propolis with silicon compounds was more durable against C. puteana than untreated wood [36,39].…”
Section: Decay Testmentioning
confidence: 94%
“…The changes in the FTIR spectrum of the wood following the action of brown-rot fungi, including C. puteana, which selectively decay carbohydrates and limit lignin degradation, have been described in the literature [34,[42][43][44][45][46][47]. The most important changes in the spectrum of wood exposure to C. puteana were observed in the fingerprint region, between 1800 and 600 cm −1 and were characterized on the basis of the literature data [13,33,[42][43][44][45][46][47].…”
Section: Ftir Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However promising in wood protection against fungi, caffeine turned out to be easily leachable from wood, which is its main disadvantage precluding it from application for wood used outdoors [ 116 ]. Therefore, several attempts have been made to stabilise caffeine inside the wood structure using organosilicon compounds [ 117 ] or a mixture of silanes and propolis [ 118 ].…”
Section: Antifungal Substances Of Plant Originmentioning
confidence: 99%
“…There is a need to develop and implement measures to prevent and eliminate the consequences of bio-damage to various building materials and structures. Specifically, the mineral bischofite allows for an effective environmental safety of materials and operation of building facilities [8,9]. Bischofite (MgCl 2 • 6H 2 O) is the most soluble natural salt, extracted to the surface by underground dissolution with fresh water; in terms of the total activity of natural radionuclides, it refers to a first class and can be used without restrictions.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%